Harnessing the nutraceutical and therapeutic potential of Allium spp.: current insights and future directions - Gorrepati, Kalyani; Krishna, Ram; Singh, Saurabh; Shirsat, Dhananjay V.; Soumia, P.S.; Mahajan, Vijay (Frontiers in Nutrition, 2024)
Apart from the culinary usage, Alliums are known for their therapeutic potential since antiquity. Alliums contain diverse bioactive compounds such as, sulfur-containing compounds (allicin, diallyl sulfides), flavonoids, and saponins. These compounds have demonstrated a wide range of pharmacological actions, including antioxidant, anticancer, anti-inflammatory, antimicrobial, neuroprotective, cardioprotective activities and treatment of metabolic disorders such as diabetes and hyperlipidemia. Despite encouraging preclinical results, translating these findings into clinical practice remains difficult, necessitating more rigorous human trials and molecular research. One of the major constrain in enhancing the therapeutic efficacy of these bioactive compound is to develop large-scale extraction techniques besides improving their stability, solubility, and bioavailability. The current scenario urges to focus research on optimizing the bioavailability of these compounds, evaluate their synergistic effects with existing therapies, as well as their long-term safety.This perspective article provides a comprehensive overview of the therapeutic potential of Allium spp. and suggests the key avenues for future research aiming at realising their full clinical potential.